The Principal’s Role in Driving a Successful Literacy Program at Elementary School - Prasetyaningrum, Eni; Kusumaningsih, Widya; Soedjono, Soedjono (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to describe the principal’s role in implementing the literacy program at SD Negeri 3 Gedong, Patean District, Kendal Regency, Central Java, which includes the stages of planning, implementation, monitoring, and evaluation. The research focuses on how the principal, as an instructional leader, drives the success of the literacy program through strategic planning, teacher empowerment, and community collaboration. This study employed a qualitative case study design. Data were collected through interviews with the principal, teachers, students, and parents; observations of literacy activities; and documentation such as school literacy policies, teacher journals, student portfolios, and evaluation reports. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The results indicate that the principal played a central role in four main stages: (1) participatory planning involving the literacy team and teachers; (2) implementation through 15-minute reading sessions, reading corners, and student recognition programs; (3) monitoring via academic supervision and coordination meetings; and (4) evaluation emphasizing reflection and continuous improvement. The principal’s leadership significantly strengthened the school’s literacy culture, reflected in higher student engagement, teacher participation, and parental support. The study concludes that developing principals’ capacity in literacy-based academic supervision, enhancing literacy media, and fostering school–community collaboration are key strategies to sustain a strong literacy culture.